2015
DOI: 10.5539/ijef.v7n10p151
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness and Determinants of Bank Profitability in Sub-Saharan Africa

Abstract: We analyse how competitive the banks in sub-Saharan Africa are and what determines their profitability. We use a panel data of 97 sub-Saharan African banks for the period from 2000 to 2012. Using recursive regression, there is no strong evidence to suggest a structural break. The findings indicate that on average banks have a 40% return on equity. The fixed effects indicate that both internal and external factors are influential in determining the profitability of the banks. Specifically, the cost-income ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
2
10
2
Order By: Relevance
“…This result is inconsistent with previous studies that found that the bank capital has respectively significant positive and significant negative influences on ROA (Dawood, 2014;Alkhazaleh & Almsafir, 2014). Regarding ROE, results are consistent with studies that concluded negative influence (Navapan & Tripe, 2003;Goddard et al, 2004b;Mathuva, 2009;Oino, 2015), However, they are inconsistent with other studies that concluded a positive and significant influence of capital ratio on bank profitability in many countries (Demirguc-Kunt & Huizinga, 1999;Ben Naceur, 2003;Goddard et al, 2004a;Pasiouras & Kosmidou, 2007;Sufian & Habibullah, 2010;Sufian, 2011). Since the results support H1-1 B but not H1-1 A , we accept the former and reject the later.…”
Section: Findings Discussion and Conclusioncontrasting
confidence: 39%
See 1 more Smart Citation
“…This result is inconsistent with previous studies that found that the bank capital has respectively significant positive and significant negative influences on ROA (Dawood, 2014;Alkhazaleh & Almsafir, 2014). Regarding ROE, results are consistent with studies that concluded negative influence (Navapan & Tripe, 2003;Goddard et al, 2004b;Mathuva, 2009;Oino, 2015), However, they are inconsistent with other studies that concluded a positive and significant influence of capital ratio on bank profitability in many countries (Demirguc-Kunt & Huizinga, 1999;Ben Naceur, 2003;Goddard et al, 2004a;Pasiouras & Kosmidou, 2007;Sufian & Habibullah, 2010;Sufian, 2011). Since the results support H1-1 B but not H1-1 A , we accept the former and reject the later.…”
Section: Findings Discussion and Conclusioncontrasting
confidence: 39%
“…Mathuva (2009) examined the relationship between capital structure and banks profitability (ROA and ROE) and he found that they are negatively correlated. Oino (2015) used a panel data of 97 sub-Saharan African banks for the period from 2000 to 2012 and found that capital ratio negatively and significantly influence profitability. The negative relationship can be explained by that increasing providers to a bank from the banks retained earnings in form of dividends will lead to reduce banks retained funds for growth purposes, which will reduce funds available to boost profit (Mathuva, 2009).…”
Section: Bank Capitalmentioning
confidence: 99%
“…The authors indicated that short-term funding, non-interest earning assets, and overhead are important factors in promoting banks' profits. Oino (2015) investigated how competitive the banks in sub-Saharan Africa are and what determines their profitability. They used a panel data of 97 sub-Saharan African banks for the period from 2000 to 2012.…”
Section: Banks Profitability In Cross Country Studiesmentioning
confidence: 99%
“…The higher EQTA ratio leads to low insolvency profile and more profitability. This measure has been used as independent variable in many studies by Bashir (2003) Dietricha and Wanzenried (2009), Muda et al (2013), Elgadi and Yu (2018), Jamel and Mansour (2018), Hassan and Bashir (2005), Oino (2015) and Aliyu and Yusof (2016).…”
Section: Bank Capitalization (Equity To Assets -Eqta)mentioning
confidence: 99%
“…The need for risk management in banks stems from the core nature of the banking business which revolves more around lending. Poor assets quality and low liquidity have been seen as the two key challenges of banks (Oino, 2015). Deteriorating assets quality in the banking sector has been of global concern particularly after the 2007-2009 global financial crisis.…”
Section: Introductionmentioning
confidence: 99%